We appreciate power: A multimodal critical discourse analysis of Grimes' music video posted on youtube - Enguídanos Gómez, Adrià (Université autonome de Barcelone, 2019)
The aim of this dissertation is to produce a multimodal critical discourse analysis of Grimes' video We Appreciate Power. This will serve to explore issues of ideology, identity and multilingualism in both the music video and the YouTube polylogues generated in the same web page. In this work I suggest that Grimes adopts a poststructuralist view that inherits Haraway's cyborg concept (1991) in this piece of multimedia. I claim that Grimes wanted to show the conflictive moral boundaries that the idea of the cyborg and trans-humanism casts upon Western civilization, such as the loss of free will but also the transgression of problematic dichotomies. The fact that the comment section of the video is available to use might signal that Grimes wanted to raise awareness about trans-humanism. By doing virtual ethnography research, examples of discussion about the relationship between the video and the studied polylogues will be examined regarding the notions of the cyborg and multilingualism. Keywords: cyborg, multimodal critical discourse analysis, polylogue, virtual ethnography, YouTube.
Keywords: 2000 à aujourd'hui; 2010-2019; analyse de discours; arts; arts visuels et médiatiques; culture populaire; cyborg; discipline; ethnographie; femmes* artistes; médias sociaux; mémoires/thèses; périodes historiques; ressource en ligne; thématiques; écriture des femmes*